The Analysis of Corporate Social Responsibility in One of the private universities in Kurdistan Region of Iraq - Al-Ani, Teba Ahmed; Vaddadi, Krishna Mohan; Surarchith, Navulur Krishna (Archives of Business Research, 2018)
The aim of this research paper is to analyze the corporate social responsibilities in one of private universities in Kurdistan region of Iraq. It starts with explaining the origin and the evolution of CSR, arguments with and against CSR, and then it crosses through the different views of CSR. In order to do that a quantitative method was used and a survey questionnaire from earlier research was adopted. The research setting was one of the private universities in Kurdistan region of Iraq, a sample of academic and administrative staff was chosen and a SPSS V. 23 has been used. As continuation to improve the work of the other researchers who analyzed the corporate social responsibility in higher educational institutions, this research paper will analyze the concept of the corporate social responsibility in universities in Kurdistan.